ID: 86: SAFETY OF 50, 000-100, 000 UNITS OF VITAMIN D3 PER WEEK IN VITAMIN D DEFICIENT, HYPERCHOLESTEROLEMIC PATIENTS, WITH STATIN INTOLERANCE. Issue 4 (22nd March 2016) - Jetty, V; Duhon, G; Shah, P; Prince, M; Lee, K; Goldenberg, M; Kumar, A; Glueck, CJ; Wang, P
Abstract : Background: In ∼85–90% of statin intolerant patients, vitamin D deficiency (serum 25 (OH) D <32 ng/ml) is a reversible cause of statin intolerance, usually requiring 50, 000 to 100, 000 units of vitamin D/week continuously to normalize serum vitamin D, and thus successfully allow reinstitution of statins which previously could not be tolerated because of myalgia-myositis. Specific Aim: In 274 statin intolerant patients, all with low entry serum vitamin D (<32 ng/ml, median 21 ng/ml), we assessed safety and efficacy of vitamin D supplementation (50, 000–100, 000 units/week) over treatment periods of 3 months (n=274), 3 and 6 months (n=161), 3, 6, and 9 months (n=58), and 3, 6, 9, and 12 months (n=22). Results: In the 385 patients with 3 month follow-up, taking mean 61, 000 and median 50, 000 IU of vitamin D3/week, median serum vitamin D rose from 20 to 42 ng/ml (p<0.0001); vitamin D became high (>100 ng/ml) but not toxic-high (>150 ng/ml) in 4 patients (1.0%) (101, 102, 106, 138 ng/ml). Median serum calcium was unchanged from entry (9.6 mg/dl) to 9.6 at 3 months. On vitamin D supplementation, the trend of change in serum calcium from normal-to-high or from high-to-normal did not significantly differ (McNemar S=1.0, p=0.32), and there was no significant trend in change of the calculated glomerular filtration rate (eGFR) from entry to follow-up (McNemar S=2.6, p=0.11). In the 161 patients with 3 and 6 month follow-up, taking mean 67, 000 and median 50, 000 IU of vitamin D3/week, median entry serum vitamin D rose from 21 to 42 to 44 ng/ml (p<0.0001), serum vitamin D was high (>100 but <150 ng/ml) in 2 patients at 3 months (1.2%, 101, 102 mg/ml) and in 3 (1.9%) at 6 months (101, 140, 140 ng/ml). Median serum calcium was unchanged from entry (9.7 mg/dl), at 3 and 6 months (9.7, 9.6 mg/dl, p>0.05). On vitamin D supplementation, the change in serum calcium from normal-to-high or high-to-normal was no significant trend (McNemar S=0.7, p=0.41), and no trend in change of eGFR (McNemar S=1.3, p=0.26). In the 58 patients with 3, 6, and 9 month follow-up on mean and median 71, 000 and 100, 000 IU of D3/week, median entry vitamin D rose from 20 to 37, 41, and 44 ng/ml (p<0.0001), with 1 (1.7%, 102 ng/ml), 2 (3.5%, 140, 140 ng/ml), and 0 (0%) patients high. Median serum calcium was unchanged from entry, median 9.7, 9.8, 9.6, and 9.6 mg/dl. On vitamin D supplementation, the trend of change in serum calcium from normal-to-high or high-to-normal was not significant (McNemar S=1.8, p=0.18), and no trend in change of eGFR (McNemar S=2, p=0.16). In the 22 patients with follow-up at 3, 6, 9, and 12 months on mean and median 70, 000 and 75, 000 IU of D3/week, median serum vitamin D rose from 20 to 37, to 41, to 44, and to 43 ng/ml (p<0.0001), with 1 (5%, 102 ng/ml) high, 2 (9%, 140, 140) high, 0 (0%) high, and 1 (5%, 126 ng/ml) high. Serum calcium was unchanged, median at entry 9.6, and then at 3, 6, 9, and 12 months 9.7, 9.7, 9.5, and 9.7 mg/ml. At entry serum calcium was normal in 21, none high, and one became high at 12 month follow-up. The trend of change in eGFR was insignificant, McNemar S=1.0, p=0.32. When serum D rose above 100 ng/ml in the few cases, as above, it fell into the normal range within 2 weeks by reducing the vitamin D dose by 50%. Conclusions: When 50, 000–100, 000 units of vitamin D/week are given to reverse statin intolerance in statin intolerant patients with low entry vitamin D (<32 ng/ml), it appears to be safe over up to 1 year follow-up, without toxic high serum vitamin D levels >150 ng/ml, and levels rarely >100 ng/ml, and without changes in serum calcium or eGFR.